Corporate Governance and Financial Performance of Village Credit Institution in Badung, Bali - I Gusti Ngurah Bagus Gunadi; I Gede Cahyadi Putra; Ida Ayu Ratih Manuari; Kadek Apriada (Universitas Warmadewa, 2025)
Financial performance is a crucial indicator of the development and sustainability of Village credit institutions and plays a significant role in building stakeholder trust. This study investigates the impact of Good Corporate Governance and the Tri Hita Karana culture on financial performance in Badung Regency. The research includes all 115 Village credit institutions in Badung, with Village Credit Institution heads as respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS. The findings reveal that Good Corporate Governance has a positive effect on financial performance, while the Tri Hita Karana culture strengthens this relationship. These results highlight the importance of implementing strong governance practices while integrating cultural values to enhance financial performance. Therefore, Village credit institutions management is encouraged to maintain good governance and uphold the principles of Tri Hita Karana in daily operations. This study contributes to understanding the role of corporate governance and cultural influences in financial performance. Future research should refine measurement instruments and consider additional variables, such as internal control and leadership style, to gain deeper insights into the determinants of financial performance.